An Exploratory Analysis of Employment-Related Experiences of Educators with Learning Disabilities - Susan A. Vogel; Christopher Murray; Carol Wren; Pamela B. Adelman (Educational Considerations, 2007)
The purpose of this study was to explore the general professional experiences of educators with learning disabilities, the unique skills and challenges among this group attributable to their experience as persons with learning disabilities, and their experience of schools as an employment context.
Keywords: professional; learning disabilities; sources; investigations; employment; experiences; educator